2022
DOI: 10.1007/s10661-022-09855-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aerosol Optical Depth over Indian Subcontinent during COVID-19 lockdown (March–May 2020)

Abstract: dataset was used to investigate the percentage change in AOD during pre-lockdown and lockdown period with respect to long-term mean. The key findings in the present study show that reduction in AOD level over Indian subcontinent is approximately 14.75% during the lockdown period with spatial variation in the magnitude from region to region. The level of AOD is greatly reduced in the northern part of India (~ 22.53%), whereas changes in the southern part of India are much less (~ -0.31%); this may be due to ong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…However, in this study, Moderate Resolution Imaging Spectroradiometer (MODIS) Terra 550-nm level 3 AOD product was used. It is because this data has better consistency compared to other products (Lyapustin, Wang, 2018;Gouda et al, 2022). Specifically, the dataset used in this study is daily and monthly mean combined dark target and deep blue AOD at 550 nm for land and ocean (MOD08 D3 V6.1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this study, Moderate Resolution Imaging Spectroradiometer (MODIS) Terra 550-nm level 3 AOD product was used. It is because this data has better consistency compared to other products (Lyapustin, Wang, 2018;Gouda et al, 2022). Specifically, the dataset used in this study is daily and monthly mean combined dark target and deep blue AOD at 550 nm for land and ocean (MOD08 D3 V6.1).…”
Section: Methodsmentioning
confidence: 99%
“…The impact of lockdown on the atmospheric AOD level was widely investigated. An assessment of AOD over the Indian subcontinent during COVID-19 lockdown (March-May 2020) showed the reduction in AOD level was as much as 14.75% during the lockdown period, with spatial variation found in the magnitude from region to region (Gouda et al, 2022). The comparison of AOD of Central-Eastern China (CEC) during the COVID-19 lockdown (January 24-February 29, 2020) with 2021 climatology data showed a decrement of 39.2% and 31.0% over Hubei and Wuhan, respectively (Shen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A spatial analysis of the AOD data revealed that the highest value could be found in the northeastern part of the state (which is subjected to large-scale mining activities and industrial emissions), whereas the southwestern part showed the lowest value. Gouda et al [23] used AOD data from the MODIS sensor on the Terra satellite to investigate the drop in AOD over India during the COVID-19 lockdown period. In India, the northern region has a 22.53% reduction in AOD levels, whereas the southern region has a significantly smaller drop (approx.…”
Section: Introductionmentioning
confidence: 99%
“…The satellite data can be economical to investigate surface phenomena and atmospheric chemistry over the short and long term. The TROPOspheric Monitoring Instrument or TROPOMI of Sentinel-5 Precursor or S-5 P) provides data related to aerosols, Formaldehyde (HCHO), CH has in uenced air quality at a large scale, and when it comes to monitoring studies over a small region, its effect has gone unmonitored due to a lack of ground observation stations and gaps in satellite data (Dey 2004;Baldasano 2020;Gouda et al 2022). The general objectives of this study are : (a) To estimate the major air pollutants, i.e., aerosols, methane, carbon monoxide, formaldehyde, nitrogen dioxide, and sulfur dioxide, and (b) to assess the spatial anomalies of these pollutants, including aerosol optical depth (AOD) and particulate matter (PM 2.5 ).…”
Section: Introductionmentioning
confidence: 99%